The evolution of urban water systems: societal needs, institutional complexities, and resource costs. Issue 2 (7th February 2019) - Arden, Sam; Jawitz, James W.
ABSTRACT: Urban water systems provide critical services to meet the supply, sanitation, and drainage needs of urban societies. Evolving needs have resulted in increasingly expansive infrastructure, raising questions about the sustainability of such large infrastructure investments. In this study, we demonstrate the historical interplay between growing urban water needs, the services developed to meet them, and their total resource cost. We hypothesize that needs evolve hierarchically, with predictable outcomes in the form of service progression. To test this hypothesis, we use a suite of metrics at the US national scale indicative of our proposed hierarchy levels. At the city scale, we assess the cost implications of this progression of services. We use the emergy framework to quantitatively reconstruct the historical resource requirements of supply, sanitation, and drainage services and show how evolving needs lead to mounting resource costs. Lastly, we discuss implications of continually increasing complexity for meeting future water needs.